1996
DOI: 10.1172/jci118621
|View full text |Cite
|
Sign up to set email alerts
|

Primary preventive and secondary interventionary effects of acetyl-L-carnitine on diabetic neuropathy in the bio-breeding Worcester rat.

Abstract: The abnormalities underlying diabetic neuropathy appear to be multiple and involve metabolic neuronal and vasomediated defects. The accumulation of long-chain fatty acids and impaired ␤ -oxidation due to deficiencies in carnitine and/or its esterified derivatives, such as acetyl-L -carnitine, may have deleterious effects. In the present study, we examined, in the diabetic bio-breeding Worcester rat, the shortand long-term effects of acetyl-L -carnitine administration on peripheral nerve polyols, myoinositol, N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
75
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(76 citation statements)
references
References 28 publications
0
75
1
Order By: Relevance
“…Our results are in contrast to studies that demonstrate neuroprotective and pro-regenerative ALCAR effects in other nerve injury models (Fernandez et al, 1991;Pacifici et al, 1992;Lowitt et al, 1995;Sima et al, 1996Sima et al, , 2005Hart et al, 2002Hart et al, , 2004aHart et al, , 2004bDeGrandis and Minardi, 2002;Wilson et al, 2003Wilson et al, , 2007Chiechio et al, 2006;Youle et al, 2007). Pisano et al (2003) showed that a prophylactic ALCAR treatment protocol prevented the decrease in the sensory nerve conduction velocity (SNCV) seen after paclitaxel and cisplatin.…”
Section: Alcar and The Paclitaxel-evoked Degeneration Of Ienfscontrasting
confidence: 96%
See 1 more Smart Citation
“…Our results are in contrast to studies that demonstrate neuroprotective and pro-regenerative ALCAR effects in other nerve injury models (Fernandez et al, 1991;Pacifici et al, 1992;Lowitt et al, 1995;Sima et al, 1996Sima et al, , 2005Hart et al, 2002Hart et al, , 2004aHart et al, , 2004bDeGrandis and Minardi, 2002;Wilson et al, 2003Wilson et al, , 2007Chiechio et al, 2006;Youle et al, 2007). Pisano et al (2003) showed that a prophylactic ALCAR treatment protocol prevented the decrease in the sensory nerve conduction velocity (SNCV) seen after paclitaxel and cisplatin.…”
Section: Alcar and The Paclitaxel-evoked Degeneration Of Ienfscontrasting
confidence: 96%
“…Paclitaxel also causes degeneration of the sensory neurons' intraepidermal terminal arbors, without degeneration of the parent axons in the peripheral nerve, and it activates cutaneous Langerhans cells . ALCAR has been shown to have neuroprotective and pro-regenerative effects following primary afferent neuron axotomy (Fernandez et al, 1991;Chiechio et al, 2006;Hart et al, 2002Hart et al, , 2004aWilson et al, 2003Wilson et al, , 2007, in the peripheral neuropathy produced by antiretroviral chemotherapy (Hart et al, 2004b;Youle et al, 2007), and in diabetic peripheral neuropathy (Lowitt et al, 1995;Pacifici et al, 1992;Sima et al, 1996Sima et al, , 2005DeGrandis and Minardi, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…This system is programmed to assess the total complement of sural nerve myelinated fibres and provides the following parameters: fascicular area (μm 2 ), number of fibres, fibre density (number/mm 2 ), mean fibre area (μm 2 ), mean axonal area (μm 2 ), mean myelin area (μm 2 ), axon/myelin ratio, and index of circularity and fibre occupancy rate (in %) as previously described [19].…”
Section: Methodsmentioning
confidence: 99%
“…α-lipoic acid, acetylcysteine and α-tocopherol) [27][28][29], γ-linolenic acid-containing oils [30] or acetyl-L-carnitine [31] have also been shown to produce some benefits on nerve function and even morphology in experimental diabetic models. However, a more detailed description of the diverse range of interventions would far exceed the scope of this text.…”
Section: Experimental Datamentioning
confidence: 99%